The Challenge of Effective Vocabulary Teaching - Cárdenas B. Melba Libia (Profile: Issues in Teachers' Professional Development)
Helping students develop vocabulary competence is one of the main challenges English language teachers face. This paper addresses the main aspects we should consider when planning and developing lessons in terms of vocabulary improvement. To achieve that objective, we will analyse the linguistic background and principles of vocabulary teaching and learning, as well as some ways of opening up vocabulary.